2002
DOI: 10.1007/bf03402155
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Anti-La/SSB Response in Sera From Patients With Sjogren’s Syndrome by Specific Blocking of Anti-idiotypic Antibodies to La/SSB Antigenic Determinants

Abstract: Background: Autoantigen La/SSB is molecular target of humoral autoimmunity in patients with primary Sjogren's Syndrome (pSS) and systemic lupus erythematosus (SLE). In this study, we investigated the existence and possible influence of anti-idiotypic response to anti-La/SSB antibodies. Materials and Methods: Synthetic peptide analogs (pep) of the major antigenic determinants of La/SSB (289-308aa and 349-364aa) were prepared. Based on "molecular recognition" theory, complementary peptides (cpep), derived by ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 59 publications
3
42
0
Order By: Relevance
“…The fact that RF is an antiidiotypic antibody in relation to anti-collagen autoantibodies, as well as the dependence of anti-collagen antibodies level from RF production level in arthritic and resistant rats, allow suggesting that rheumatoid factor and RF-producing lymphocytes are involved in regulation of anti-collagen autoreactive lymphocyte activity through IAI interactions. This does not contradict the contemporary knowledge of regulatory functions of anti-idiotypic antibodies and lymphocytes (Zanetti et al, 1991;Routsias et al, 2002;Wu et al, 2007;Calkins et al, 1990;Zhang, 2004). Therefore we do not exclude a direct activation of autoreactive anti-RCII lymphocytes by bovine collagen and can suppose that induction of anti-collagen autoreactive lymphocytes needs a Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The fact that RF is an antiidiotypic antibody in relation to anti-collagen autoantibodies, as well as the dependence of anti-collagen antibodies level from RF production level in arthritic and resistant rats, allow suggesting that rheumatoid factor and RF-producing lymphocytes are involved in regulation of anti-collagen autoreactive lymphocyte activity through IAI interactions. This does not contradict the contemporary knowledge of regulatory functions of anti-idiotypic antibodies and lymphocytes (Zanetti et al, 1991;Routsias et al, 2002;Wu et al, 2007;Calkins et al, 1990;Zhang, 2004). Therefore we do not exclude a direct activation of autoreactive anti-RCII lymphocytes by bovine collagen and can suppose that induction of anti-collagen autoreactive lymphocytes needs a Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, naturally occurring anti-Id Ab against AChR Ab has been reported in 40% of human MG patients, and its presence is associated with lower anti-AChR Ab titers and clinical improvement (Dwyer et al, 1983;Dwyer et al, 1984). Furthermore, in other Ab-mediated autoimmune disorders, including systemic lupus erythematosus, Sjogren's syndrome and autoimmune necrotizing systemic vasculitis, anti-Id Ab that binds autoreactive Ab can be detected with the appropriate complementary/ARM peptides (Pendergraft et al, 2004;Routsias et al, 2002;Routsias et al, 2003). Thus, B cell vaccines of the type herein described may be useful in inducing or bolstering a natural and perhaps regulatory anti-Id Ab response in not only MG but other adult autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…They also recognize recombinant La/SSB, but not recombinant Ro60 or Ro52 in enzyme-linked immunosorbent assays (ELISA) (data not shown). Moreover, previous studies from our laboratory have demonstrated the specific recognition of La/SSB by these autoantibodies [12].…”
Section: Specificity Of Purified Anti-la/ssb Antibodiesmentioning
confidence: 99%